2005
DOI: 10.1111/j.1540-8159.2005.50154.x
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful AV Nodal Ablation in Atrial Fibrillation: An Alternative Method to Achieve Complete Heart Block

Abstract: We report the case of an elderly patient who presented with poorly tolerated episodes of atrial arrhythmia refractory to medical treatment. AV node ablation was identified as the only alternative expected to be efficacious for symptom relief. However, this usually simple intervention failed. The goal of creating a complete AV block was finally achieved through ablation of the anterior fascicle of the His bundle, which represented the only pathway for residual conduction in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Beside the above‐mentioned mechanisms, tachycardia‐ (phase 3) and bradycardia‐ (phase 4) dependent conduction block may be responsible for intermittent preexcitation 3–5 . The latter (alone or in combination with the above‐mentioned mechanisms) could be responsible for the block that was observed in Figure 1B 1 . Some patients with accessory pathway have a narrow conduction window with a range of 20–160 ms which is responsible for intermittent preexcitation and conduction block 5 especially during atrial fibrillation (concealed conduction) as in this patient 4 …”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Beside the above‐mentioned mechanisms, tachycardia‐ (phase 3) and bradycardia‐ (phase 4) dependent conduction block may be responsible for intermittent preexcitation 3–5 . The latter (alone or in combination with the above‐mentioned mechanisms) could be responsible for the block that was observed in Figure 1B 1 . Some patients with accessory pathway have a narrow conduction window with a range of 20–160 ms which is responsible for intermittent preexcitation and conduction block 5 especially during atrial fibrillation (concealed conduction) as in this patient 4 …”
mentioning
confidence: 93%
“…Sunthorn et al in a recent case report in the Journal have reported a case in which AV node ablation was impossible to perform, neither by right‐ nor by left‐sided access 1 . However, after a close look at the presented ECG (Fig.…”
mentioning
confidence: 96%
See 2 more Smart Citations